The role of the university in recovering from COVID-19 and preparing for future crises- perspectives and experiences from Sunway University, Malaysia - Elil, Renganathan *; Guinto, Renzo R *; Jemilah, Mahmood *; Lacey-Hall, Oliver; Abhi, Veerakumarasivam *; Poppema, Sibrandes * (Frontiers Media, 2023)
This article is part of the Research Topic 'Health Systems Recovery in the Context of COVID-19 and Protracted Conflict'. Universities, as engines of knowledge creation and dissemination and as incubators of disciplined yet original thinking, have a key role to play in tackling the most complex challenges that societies and our planet face, from infectious diseases to the climate emergency. This commentary presents the perspectives from Sunway University, a young private university in Malaysia that made a strong commitment to the sustainable development goals (SDGs) prior to the pandemic, and its experiences in promoting research, innovation, and learning as part of COVID-19 recovery and in preparation for future crises such as the climate emergency. Some of the university's initiatives include embracing the planetary health approach, reviving essential public health functions, exploring pandemic resilience, addressing 'infodemics' and promoting science diplomacy. The example of Sunway University provides some insights on the opportunities and challenges that academic institutions face as they seek to reorient the paradigm of education, research, and service away from disciplinary siloes and towards a more integrated, preventive, accessible and translational approach.